Simultaneous determination of 17 antiretroviral drugs in human plasma for quantitative analysis with liquid chromatography-tandem mass spectrometry - Jung, Byung Hwa; Rezk, Naser L.; Bridges, Arlene S.; Corbett, Amanda H.; Kashuba, Angela D. M. (WILEY, 2007)
This work describes a sensitive method for the simultaneous determination of 17 antiretroviral drugs including nucleoside analog reverse transcriptase inhibitors, non-nucleoside analog reverse transcriptase inhibitors, protease inhibitors and a nucleotide analog reverse transcriptase inhibitor in 50 mu L of human plasma. This method employed high-performance liquid chromatography-tandem mass spectrometry with electrospray ionization. The analytes were monitored in multiple reaction monitoring mode and the polarity was switched from positive to negative to positive to detect all compounds after a single injection. A combination of liquid-liquid extraction and protein precipitation was used to extract all compounds, with at least 75% recovery for all analytes. Within- and between-day accuracies were at least 85% for 1-500 ng/mL for nelfinavir, indinavir and abacavir, 10-500 ng/mL for didanosine and stavudine and 5-500 ng/mL for all other compounds. This method is very effective for quantifying and screening antiretroviral drugs in clinical samples with limited (50 mu L) volumes. Copyright (c) 2007 John Wiley & Sons, Ltd.
Keywords: REVERSE-TRANSCRIPTASE INHIBITORS; HIV PROTEASE INHIBITORS; BLOOD MONONUCLEAR-CELLS; RAPID QUANTIFICATION; NEVIRAPINE; THERAPY; INDINAVIR; AMPRENAVIR; SAQUINAVIR; ATAZANAVIR